Surgical Outcomes of Pediatric Craniopharyngiomas in Nepal: A Prospective Observational Study - Kumar, Paudel; Binod, Rajbhandari; Sameer, Aryal; Mohan, Bhattarai Sushil; Shrestha, Rajendra; Rajiv, Jha (Nepal Journal of Neuroscience, 2026)
Background: Craniopharyngiomas are benign tumor of skull base which often follows an aggressive clinical course. Adamantinomatous subtype are frequently observe in age group 5-15 years. Currently, treatment strategy has relied exclusively on surgery and radiotherapy. Materials and Methods: All pediatric Craniopharyngiomas operated at National Neurosurgical Referral Center, Bir hospital from Nov 2021 to Dec 2023 were included in this study. Results: A total of 17 patients underwent surgical excision of craniopharyngioma. The male to female ratio was 4.6:1. The mean age of the patients was 10.88 ± 4.18 (Range 2 to 16 years). The most common presenting symptoms were headache (64.7%) followed by visual disturbances.12 patients exhibited preoperative hypothalamic pituitary axis dysfunction including central hypothyroidism (35.6%), central diabetes insipidus (29%), growth hormone deficiency (35.6%), adrenocortical insufficiency (23.5%). The Gross total resection was achieved in 6 patients (45%) while subtotal resection was done in remaining 11 patients (55%). Modified Rankin scale score (mRS) on discharge was favorable outcome (mRS 0,1,2,3) in 75% and unfavorable outcome (mRS 4,5) in 19%. There was one mortality. The overall rate of postoperative Diabetes insipidus (DI) was 35.3 % (6/17), visual deterioration (6%), meningitis (11.7%) behavioral disturbances (6%). On 6 month follow up MRI, recurrence was noted in 5 cases, 3(50%) in cases with gross total resection and 2(18.2%) in subtotal resection with adjuvant radiotherapy group. Conclusion: We conclude that Surgical excision of pediatric craniopharyngioma caries a substantial risk of postoperative hypothalamic pituitary dysfunction which significantly impair the quality of life and functional recovery of these patients. A high index suspicion of hypothalamic involvement by tumor and its preservation can improvise patient functional outcome. Postoperative radiotherapy is advised in patient with subtotal resection to improve recurrence free survival.